PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KEPUASAN KERJA GURU DI SEKOLAH MENENGAH KEJURUAN BISNIS INDONESIA - Muhammad Rizky Fadlillah Kurdi (2022)
The purpose of this study was to determine whether there is an influence of organizational culture, leadership style, and compensation variables on teacher job satisfaction at Bisnis Indonesia Vocation School. This research is a quantitative research with primary data sources. The object of this research is the teacher at the Bisnis Indonesia Vocational School with a sample of 30 respondents using the saturated sample technique as a sampling technique. The data analysis technique used is descriptive and inferential data analysis technique. Based on the results of data processing through t-statistics on Smart PLS, it can be shown that organizational culture has a significant positive effect on job satisfaction behavior, with an original sample value of 0.702 and a significance value of 0.000. Then leadership style has a significant positive effect on job satisfaction, with an original sample value of 0.343 and a significance value of 0.015. And then compensation has a significant negative effect on job satisfaction with the original sample value -0.169 and a significance value of 0.037. From the results of the study, it is better for the Bisnis Indonesia Vocational School to increase attention to all the needs of teachers and how the condition of the teacher is so that the teacher feels comfortable and achieves job satisfaction.